MEMORY AND COLOR: CHROMATIC INTERVENTIONS IN THE HISTORICAL LANDSCAPE OF CURITIBA - Adamante, Ana Claudia (Seven Editora, 2024)
This article analyzes the contemporary phenomenon of "rejuvenation" in urban landscapes, specifically through chromatic interventions, and its implications for the preservation of historical and cultural values. The study discusses the concern with cultural pasteurization and the degradation of historic centers, showing that chromatic interventions can result in disordered and questionable landscapes. In addition, the relationship between landscape and memory is addressed, emphasizing the social construction of collective memory. Color, understood as a constitutive element of the landscape, expresses historical and cultural values that connect history and local identity. Focusing on Largo da Ordem in Curitiba, the research reflects on how these interventions impact the symbolic identity of the historical space, questioning the role of a globalized aesthetic in the local cultural context. The methodology involves a bibliographic survey that explores the relationship between landscape, memory and color, analyzing the importance of color in the identity of historic centers. The article concludes that the contemporary desire for rejuvenation has profound implications for the preservation of historical heritage, challenging local identity in a world that values novelty over historical density. The analysis of chromatic interventions in the Curitiba landscape exemplifies the need to balance urban revitalization with the preservation of memory and local cultural identity. DOI:https://doi.org/10.56238/sevened2024.037-001